LITERASI INFORMASI MAHASISWA DALAM PEMANFAATAN MEDIA SOSIAL TIKTOK DI UNIVERSITAS MUHAMMADDIYAH ENREKANG - Fhatin Nurul Asikin; Andi Ahmad Chabir Galib; Muhammad Nasrul; Ismaya; Syahdan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to identify the forms of students’ information literacy in utilizing TikTok as a source of information and to examine the challenges they face in applying information literacy while using TikTok at Universitas Muhammadiyah Enrekang. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, and were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings reveal that students of Universitas Muhammadiyah Enrekang demonstrate a fairly good level of information literacy in utilizing TikTok as a source of information. This is reflected in their ability to search for, select, evaluate, verify, and utilize information to support academic needs and broaden their knowledge. Students also verify and compare information with more credible sources, such as books, scientific journals, official websites, and trusted media outlets. In addition, TikTok is used as a medium for accessing educational content, course materials, and learning tutorials. However, students still encounter several challenges, including difficulties in distinguishing accurate information from misinformation, the lack of clear references or sources, the rapid spread of unverified information, the short duration of videos, the dominance of entertainment content, the influence of TikTok’s algorithm, and limitations related to internet connectivity and data quotas. Therefore, critical thinking, information verification, and digital literacy skills need to be continuously strengthened so that TikTok can be used wisely and responsibly as a source of information.